Postpartum depression in an Indian community: more prevalent less addressed issue - Nigam, Aruna; Prakash, Anupam; Maheshwari, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Postpartum depression is major health concern which not only has effect on maternal mortality and morbidity but also have effect on the cognitive and behavioral development of the child. Aims of the study was to study the prevalence of postpartum depression and its correlates. Methods: 100 women between 2 to 6 weeks of postpartum period were subjected to a pre-tested pre-structured standard questionnaire. Diagnosis of depression was made using the Edinburgh Postnatal Depression Scale. Possible depression is suggested by a score of 10 or greater; while values equal to 13 or more are invariably associated with depression. Results: The average age of the study group was 28.67±5.22 years and average duration of the post-partum period was 28.12±10.94 days. There was only one single parent in the study group; 77% were Hindus, 23% Muslims; 72% were housewives, while 22% were laborers. All subjects belonged to the low or middle socioeconomic groups. One-third of the subjects were illiterate. 93% had scores > 13 by use of the Edinburgh Postnatal Depression Scale. 89% of the subjects had five or more contributory factors out of 21 contributory factors studied. The most common contributory factors were- child care stress, life stress, low self-esteem, low social support, infant temperament problems, low socioeconomic status, prenatal depression and prenatal anxiety. Conclusions: There is high prevalence of postpartum depression outskirts of Lucknow. Thus it appears pertinent to screen all women for postpartum depression after child-birth in this area so as to improve maternal and child health.